Questions Answered and Unanswered by the First CRISPR Editing Study in a Canine Model of Duchenne Muscular Dystrophy - Wasala, Nalinda B. (Hum Gene Ther, 2019)
Clustered regularly interspaced short palindromic repeats (CRISPR) editing is being considered as a potential gene repair therapy to treat Duchenne muscular dystrophy, a dystrophin-deficient lethal muscle disease affecting all muscles in the body. A recent preliminary study from the Olson laboratory (Amoasii et al. Science 2018;362:89–91) showed robust dystrophin restoration in a canine Duchenne muscular dystrophy model following intramuscular or intravenous delivery of the CRISPR editing machinery by adeno-associated virus serotype 9. Despite the limitation of the small sample size, short study duration, and the lack of muscle function data, the Olson lab findings have provided important proof of principle for scaling up CRISPR therapy from rodents to large mammals. Future large-scale, long-term, and comprehensive studies are warranted to establish the safety and efficacy of CRISPR editing therapy in large mammals.